Comparative study of online shopping methods in Spain - Yustres Duro, Pilar; Melendo Rodríguez-Carmona, Laura (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This article will analyse the different online shopping methods available to Spanish consumers, focusing on the purely online shopping method, show-rooming, ROPO, BOPIS and BORIS. This analysis will be followed by a comparison of which shopping methods are preferred by Spanish shoppers after the COVID-19 pandemic and the possible causes of this decision.